Methylviologen resistance in loss-of-function mutants of the polyamine transporter gene OsLAT5 - Kyrylo Schenstnyi; Zhengzhi Zhang; Bo Liu; Masayoshi Nakamura; Van Schepler-Luu; Eliza P. I. Loo; Bing Yang; Wolf B. Frommer (PLoS ONE, 2026)
TALENs and CRISPR/Cas have become routine tools for genome editing. During stable plant transformation, genes coding for editing enzymes, e.g., Cas9, guide RNAs (gRNA), and selectable or screenable markers are integrated into the nuclear genome. Identification of successful transformants relies on selectable or screenable markers, typically genes providing resistance to herbicides or antibiotics. Selectable markers use a substantial portion of the T-DNA, hence reducing transfer efficiency by limiting the effective number of TALENs or guide/pegRNAs that can be used. Marker genes are frequently subject to gene silencing. Here, we generated loss-of-function mutations in PUT/LAT-type polyamine transporter family genes to confer resistance to methylviologen (MV) in rice. As proof of concept, CRISPR/Cas9 constructs with gRNAs were generated to target three close homologs, namely OsLAT1 , OsLAT5 , and OsLAT7 . Loss of OsLAT5 (also known as OsPUT3 or OsPAR1 ) function was sufficient to confer resistance to MV in rice seeds, seedlings and calli. Loss-of-function alleles generated by editing of LAT5 can serve as a selectable marker at the seed germination stage. We discuss the potential utility of rice lat5 loss of function variants as selectable markers for genome editing.